Evolutionary Systems Biology - Soyer, Orkun S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
The book aims to introduce the reader to the emerging field of Evolutionary Systems Biology, which approaches classical systems biology questions within an evolutionary framework. An evolutionary approach might allow understanding the significance of observed diversity, uncover “evolutionary design principles” and extend predictions made in model organisms to others. In addition, evolutionary systems biology can generate new insights into the adaptive landscape by combining molecular systems biology models and evolutionary simulations. This insight can enable the development of more detailed mechanistic evolutionary hypotheses.
Preface -- Evolutionary Systems Biology: Historical and Philosophical Persepctives on an Emerging Synthesis -- Metabolic Networks and their Evolution -- Organization Principles and their Evolution -- Organization principles in genetic interaction networks -- Evolution of regulatory networks: Nematode vulva induction as an example of developmental systems drift -- Life’s attractors understanding developmental systems through reverse engineering and in silico evolution -- Evolutionary characteristics of bacterial two-component systems -- Comparative interaction networks - bridging genotype to phenotype -- Evolution in silico: from network structure to bifurcation theory -- On the search for design principles in biological systems -- Towards a theory of multilevel evolution; long term information integration shapes the mutational landscape and enhances evolvability -- Evolutionary principles underlying structure and response dynamics of cellular networks -- Phenotypic plasticity and robustness: Evolutionary stability theory, gene expression dynamics model, and laboratory experiments -- Genetic redundancies and their evolutionary maintenance -- Evolution of resource and energy management in biologically realistic gene regulatory network models -- Reverse ecology: From systems to environments and back -- Bacteria-virus coevolution -- The genotype-phenotype maps of systems biology and quantitative genetics: distinct and complementary -- How evolutionary systems biology will help understand adaptive landscapes and distributions of mutational effects -- Building synthetic systems to learn Nature’s design principles -- The robustness continuum -- Index.
Keywords: Systems biology; Evolutionary biology; Medicine; Systems Biology; Evolutionary Biology; Biomedicine, general